2009
DOI: 10.1093/czoolo/55.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the greater bandicoot rat Bandicota indica (Rodentia: Muridae) in the rice fields of southern Thailand

Abstract: This study investigated some aspects of the reproductive biology of male and female greater bandicoot rats, Bandicota indica, in southern Thailand from September 2004 to September 2006. In females, body, uterine and preputial gland weights, occurrences of pregnancies and placental scars, and in males, testicular weights and histology, and sizes of accessory sex glands, were recorded. Pregnancies occurred predominantly, but not exclusively, in the wet season, with a higher incidence pregnancies in the second, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Although it has recently been suggested that the reason for the highly divergent sperm, and its absence of an apical hook, of B. indica may be due to depressed levels of intermale sperm competition since this species has a relatively small testis mass (Thitipramote et al 2009(Thitipramote et al , 2011, the current findings point to a co-evolution of the sperm and egg coats that may relate to divergent processes of sperm-egg interaction at the time of fertilisation. Clearly, a study on the events of fertilisation in the Greater Bandicoot Rat is now required to test this hypothesis.…”
Section: )contrasting
confidence: 67%
See 2 more Smart Citations
“…Although it has recently been suggested that the reason for the highly divergent sperm, and its absence of an apical hook, of B. indica may be due to depressed levels of intermale sperm competition since this species has a relatively small testis mass (Thitipramote et al 2009(Thitipramote et al , 2011, the current findings point to a co-evolution of the sperm and egg coats that may relate to divergent processes of sperm-egg interaction at the time of fertilisation. Clearly, a study on the events of fertilisation in the Greater Bandicoot Rat is now required to test this hypothesis.…”
Section: )contrasting
confidence: 67%
“…; Thitipramote et al . , ). These latter features suggest that the sperm of the Greater Bandicoot Rat, as well as that of its sister species B. savilei , show, in some regards, convergence to the sperm of the distantly related Naked Mole Rat, Heterocephalus glaber (Van der Horst et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether this observed variability is because of the obtaining of the sperm samples from individuals that were optimally reproductive active, is not known. A recent study of B. indica collected in the wild over a 2‐year period has shown that these animals reproduce during the rainy season, with some reproductive activity extending into the following dry period for a variable length of time (Thitipramote et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An early report from Bombay and Calcutta (1966) showed that B. bengalensis increased in population size enormously and displaced the R. rattus in urban areas (Seal & Banerji, 1966). One of the underlying mechanisms was the high reproductive capacity of B. bengalensis (Parrack & Thomas, 1970;Smiet, Fulk, & Lathiya, 1980;Thitipramote, Suwanjarat, & Breed, 2009), and the aggressive behaviour that dominant males exhibit (Parrack & Thomas, 1970;Smiet et al, 1980). Other research from India reported B. bengalensis to be the most aggressive field rodent (Mann, 1973) and that the females confine most of their time to hoarding food and are less active than males (Parrack & Thomas, 1970).…”
Section: Discussionmentioning
confidence: 99%